If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4(x+1)-3=5(x+2)+3
We move all terms to the left:
4(x+1)-3-(5(x+2)+3)=0
We multiply parentheses
4x-(5(x+2)+3)+4-3=0
We calculate terms in parentheses: -(5(x+2)+3), so:We add all the numbers together, and all the variables
5(x+2)+3
We multiply parentheses
5x+10+3
We add all the numbers together, and all the variables
5x+13
Back to the equation:
-(5x+13)
4x-(5x+13)+1=0
We get rid of parentheses
4x-5x-13+1=0
We add all the numbers together, and all the variables
-1x-12=0
We move all terms containing x to the left, all other terms to the right
-x=12
x=12/-1
x=-12
| 5(x-3)=7(3x+2) | | 9x-5x=3x+8 | | 3x=13-25 | | -12=-5x+33 | | 4/15x=25 | | 5-3x=2+10 | | x²+4x=64 | | 5(-2y+10)=60 | | x+(5+x)=80 | | -3(-4y+4)=48 | | -2(5y+-7)=24 | | 0.02x+0.9=0 | | (7)/(2)=(x+2)/(4) | | x*x-6x=25 | | (4x+10)+(2x+40)=180 | | (x/32)=0.56 | | (x-32)=0.56 | | 7x+48=1 | | 5x^2+10x+39=0 | | 8-9z=10 | | 15x+7=0.5x | | n×n=22 | | 7x+23x-10=6(5x+9) | | 11x+3=-16 | | -28=3(x-3)+5 | | 9x+19=-15 | | 5x+85=5x+5 | | -3=4(x+2)+1 | | 25+8n=8(n+3)+1 | | 3(2x+5)=-3x+6 | | 3(4x-2)+9=15 | | 0.2x=-6 |